Constructing a model of the factors related to the job wellbeing of preschool teachers in China: a grounded theory study - Nong, Li-Ying; Liao, Chen; Ye, Jian-Hong (Frontiers in Public Health, 2025)
IntroductionAs educational management research evolves, leadership styles are increasingly recognized as crucial managerial skills. Among various leadership approaches, empowering leadership has been found to significantly enhance employee job performance and satisfaction. However, there is limited research exploring the relationship between empowering leadership and the job wellbeing of preschool teachers in the educational sector.MethodsThis study examines the relationship between empowering leadership and preschool teachers' job wellbeing using the Job Demands-Resources (JD-R) model. Semi-structured interviews were conducted with 12 preschool teachers and 12 kindergarten leaders in China. The qualitative data collected were analyzed using grounded theory to identify themes and construct a systematic model.ResultsThe findings suggest that empowering leadership of kindergarten principals is positively related to preschool teachers' job wellbeing. This relationship is mediated through stress pathways, such as work pressure and burnout, as well as through enhanced organizational support and a positive work environment. Furthermore, empowering leadership influences teachers' personal motivation and work engagement, which in turn impacts their job wellbeing.DiscussionThe study highlights the importance of empowering leadership in improving preschool teachers' wellbeing. By addressing stress factors, enhancing organizational support, and promoting personal motivation, empowering leadership can foster a more supportive and engaging work environment. These findings have practical implications for leadership practices in early childhood education settings.